Comparative Analysis of infiltration Area Regulations: A Study of Ministerial Regulation No. 10/2015 on Public Works and Public Housing Versus Ministerial Regulation No. 10/2022 on Environment and Forestry with a Focus on Rupat Island, Indonesia - Manyuk Fauzi; Yohanna Lilis Handayani; Reski Seftiyansyah; Randhi Saily (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2026)
Groundwater sustainability on small islands depends heavily on effective infiltration zones that support natural recharge. Rupat Island in Indonesia faces declining groundwater levels and seawater intrusion, raising the need for accurate infiltration mapping. This study aims to compare the suitability and sensitivity of two national regulatory frameworks—Ministerial Regulation No. 10/2015 (Public Works and Public Housing) and Ministerial Regulation No. 10/2022 (Environment and Forestry)—in delineating infiltration areas. A GIS-based weighted overlay analysis was applied using rainfall, slope, land use, and soil type parameters, following the classification standards of each regulation. The results show substantial discrepancies: the 2022 framework identifies 5.86% of the island as critical infiltration areas, while the 2015 framework identifies only 0.001%. These differences are statistically confirmed through a two-way ANOVA (p < 0.05), indicating that the ecological emphasis of the 2022 regulation produces more conservative classifications. The findings imply that regulatory interpretation significantly influences groundwater zoning, especially on ecologically sensitive small islands. The study contributes theoretically by demonstrating how policy frameworks shape spatial hydrological assessments, and practically by providing evidence-based guidance for local authorities to improve infiltration protection, land-use planning, and groundwater management strategies.